Global-Scale Flow Routing for Load-Balancing in In-Band Software-Defined MANET - Thananop Thongthavorn; Sumet Prabhavat (IEEE Access, 2025)
Mobile Ad Hoc Networks (MANETs) typically operate with limited resources; therefore, achieving better load distribution among mobile nodes can significantly enhance network performance by improving resource utilization. In distributed load-balancing protocols, a lack of global network topology information causes source nodes to make load-balancing routing decisions without awareness of other active paths. As a result, overlapping paths from different source nodes tend to be formed, increasing network congestion and packet collision probability, which ultimately degrades network performance. A Software-Defined MANET (SD-MANET) is a promising solution to this problem since the controller can make a routing decision for source nodes based on up-to-date network topology snapshots. In this paper, we propose a global-scale flow routing algorithm based on an in-band SD-MANET architecture. Once the controller aggregates local network data into a global topology view, it can identify a path that avoids using any nodes currently serving as a relay in other active paths. The controller then establishes or switches the active flow to the new route depending on the current network situation. Simulation results show that our proposed work can effectively reduce the number of overlapping paths, resulting in lower load balancing errors and a higher packet delivery ratio.
Keywords: Mobile Ad Hoc Networks; Wireless Networks and Protocols; Energy Efficient Wireless Sensor Networks